Cell-free immunomodulatory biomaterials mediated in situ periodontal multi-tissue regeneration and their immunopathophysiological processes. (December 2022) - Liu, Guanqi; Zhou, Xuan; Zhang, Linjun; Zou, Yang; Xue, Junlong; Xia, Ruidi; Abuduxiku, Nuerbiya; Xuejing Gan; Liu, Runheng; Chen, Zhuofan; Cao, Yang; Chen, Zetao
Abstract: Cell-free biomaterials-inducing endogenous in situ multi-tissue regeneration is very challenging and applying advanced immunomodulatory biomaterials can be an effective strategy to overcome it. In-depth knowledge of the immunopathophysiological mechanisms should be acquired before applying such an immunomodulation strategy. In this study, we implanted different immunoregulatory cell-free biomaterials into periodontal multi-tissue defects and showed that the outcome of multi-tissue regeneration is closely regulated by the immune reaction. The underlying immunopathophysiological processes, including the blood clotting response and fibrinoid necrosis, innate and adaptive immune response, local and systemic immune reaction, growth factors release, and stem cells recruitment, were revealed. The implantation of biomaterials with anti-inflammatory properties could direct the immunopathophysiological process and make it more favorable for in situ multi-tissue regeneration, ultimately enabling the regeneration of the periodontal ligament, the acellular cementum matrix, and the alveolar bone in the periodontium. These findings further confirm the effectiveness of immunomodulatory based strategy and the unveiling of their immunopathophysiological processes could provide some favorable theoretical bases for the development of advanced cell-free immunomodulatory multi-tissue regenerative biomaterials. Graphical abstract: Image 1